Rates and characteristics of postcolonoscopy colorectal cancer in the Swedish IBD population: what are the differences from a non-IBD population?. Issue 9 (15th December 2018) - Stjärngrim, Jessica; Ekbom, Anders; Hammar, Ulf; Hultcrantz, Rolf; Forsberg, Anna M
Abstract : Objective: The rate of postcolonoscopy colorectal cancer (PCCRC) is considered a key quality indicator of colonoscopy; little is known about PCCRC in IBD. Design: A population-based cohort study of colonoscopies in Sweden from 2001 to 2010 was conducted. Individuals with a colorectal cancer (CRC) detected within 36 months after a colonoscopy were identified and stratified on UC, Crohn's disease (CD) or non-IBD. The CRCs were classified as detected CRCs (dCRC) (0–6 months) or as PCCRCs (6–36 months). PCCRC rates were calculated by the number of false negative/(the number of true positive+the number of false negative) colonoscopies. Poisson regression analysis was employed to examine the association between PCCRC and IBD (CD and UC) diagnosis, age, gender, location, time period and comorbidities. Results: We identified 348 232 colonoscopies in 270 918 individuals. Of these, 27 123 were performed on 14 597 individuals with CD, and 51 572 were performed on 26 513 individuals with UC. There were 13 317 CRCs in the non-IBD group, 133 in the CD group and 281 in the UC group. The PCCRC rate in the CD group was 28.3% and 41.0% in the UC group. The RR for a PCCRC was 3.82 (95% CI 2.94 to 4.96) in CD and 5.89 (95% CI 5.10 to 6.80) in UC, compared with non-IBD. The highest risk was observed among rectal cancer location in CD and in younger individuals with UC. Conclusion: The high rates of PCCRC in young patients with UC and for rectal cancer location in CD might affect future performance of IBD surveillance.